Shaping Words: From Speech to Song, Linguistic Principles and Rhythmic Expressivity in Choral Performance. Issue 3 (2nd September 2019) - Ellis, Ryan
ABSTRACT: This article will explore the use of natural speech inflections according to linguistic principles in order to guide rhythmic expressivity in choral performance practice. The standard of rhythmic precision in choral elocution as it relates to serving exact durational values can often predominate over textual expression and rhetorical nuance in ensemble vocal music. The common practice in American choral tradition has a propensity to maximize the length of the primary vowel in a syllable during a given rhythmic value, which may lead to a bound and rigid performance with less prosodic shape. A better understanding of genres in a spoken style, the historical practice of note inequality, and the theoretical discourse on rhythm in language and music may allow for informed artistic flexibility in note durations for perceived accentuation. Recent empirical research, which incorporates aspects of cross-domain speech and music, offers significant insight into how we can better understand the artistic goals of aesthetic expressivity through a malleable function of time.